OPPORTUNITIES FOR IMPROVING THE MANAGEMENT SYSTEM OF THE EDUCATIONAL INSTITUTION WITH INFORMATION TECHNOLOGIES - Mardonov Obidjon Omonovich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In recent years, the education system has been fundamentally reformed in our country, and special attention is being paid to raising a mature generation who are worthy successors of our tomorrow. The implementation of such ambitious tasks places a great responsibility on the centers of retraining of preschool and school education workers and their professional development.